Designing Effective Online Learning Environments for Teacher Professional Development: Evidence from Indonesian In-Service Teachers - Apoko, Tri Wintolo; Yatri, Ika (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The teacher profession education program (TPEP) within virtuality is an alternative learning program that is believed to be important for Indonesian in-service teachers nowadays and in the future as learning through digital technology is the competitiveness of the nation that needs to be continuously improved. This study aims to investigate Indonesian in-service teachers’ needs in the TPEP through online learning environments and to discover an effective design of online learning environment for TPEP in the future. The design used in this study was a mixed method with sequential explanatory design. For quantitative data, a questionnaire was distributed to the Indonesian in-service teachers attending the online TPEP over four months at a reputable private university in Indonesia, and 916 teachers completed the questionnaire. Meanwhile, the qualitative data were collected through semi-structured interview with selected Indonesia in-service teachers. The results indicate that online learning provides in-service teachers’ needs, and effective design is recommended for better professional development for in-service teachers in Indonesia. In addition, the qualitative feedbacks from participants regarding online learning environments identify several challenges. These findings suggest that the proposed design of online TPEP can be significantly implemented to meet the evolving needs of educators in an increasingly digital world.